Integrasi Nilai Pendidikan Karakter dalam Pembelajaran IPS di Sekolah Dasar - Nashifatul Izzah; Ahmad Hidayat; Oman Farhurahman (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Education is basically a conscious effort to develop students' potential to the maximum. One important aspect of education is character education which aims to train children so that they grow into responsible individuals. Thus, character education not only helps overcome signs of moral crisis, but also plays a role in developing the younger generation. Social studies education is a science that studies social life using teaching materials based on research in the fields of history, geography, economics, sociology, anthropology and political art.